The Labarum – from Crux Dissimulata and Chi-Rho to the Open Image Cross - Bralewski, Sławomir (Studia Ceranea, 2020)
Based on the testimony of emperor Constantine the Great himself, Eusebius of Caesarea presented a labarum in the form of crux dissimulata crowned with the Chi-Rho. The continuers of his Church History in the next century, Rufinus of Aquileia, Philostorgius, Socrates of Constantinople, and Sozomen, only kept the cross-shape of the banner, excluding the christogram. This might have happened because in two main sources informing about the vision of Constantine – the accounts of Eusebius of Caesarea and Lactantius – it was not only the monogram of Christ that played a significant role. The motif of the cross also appears in them, in the account of Eusebius directly, and Lactantius indirectly. Furthermore, Christians interpreted the cross explicitly as a sign of victory. Eusebius wrote about the cross as a symbol of immortality, a triumphant sign of Christ overcoming death. In the account of the bishop of Caesarea, on the other hand, Constantine’s supposed vision included a triumphal sign in the form of a luminous cross, or the symbol of the trophy of salvation. Numismatic evidence also cannot be ignored. Already during the reign of Constantine the Great, the Chi-Rho appeared on the coins both on the shields and on the labarum. However, starting from the reign of Constantius II, coins that were minted included the cross instead of the Chi-Rho on the labarum. It also began to be placed on the shields, in their central part, where the monogram of Christ used to be. Over time, the cross replaced the entire labarum. The iconography present on the coins may prove that the phenomenon of identifying the labarum or Chi-Rho with the cross was not limited to church historiography and was more widespread, although it should be remembered that coins continued to also be decorated with the letters Chi-Rho. Therefore, the representation of the cross did not replace this symbol. However, it cannot be ruled out that the increasingly common image of the cross on coins also contributed to the aforementioned perception of the labarum by church historians.